Potensi Bakteri Endofit Andaliman (Zanthoxylum Acanthopodium DC.) Menghambat Bakteri Penyebab Infeksi pada Manusia - Debie Rizqoh; Wulan Okta Kumala; Sipriyadi Sipriyadi; Besly Sinuhaji; Oktoviani Oktoviani (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
Endophytic bacteria are a beneficial bacteria that live in plant tissue. Several studies have shown that certain endophytic bacteria can produce secondary metabolites that have health effects. The andaliman (Zanthoxylum acanthopodium DC) have several properties, one of which is as antibacterial against pathogenic bacteria. The most common bacterial infections in humans are caused by commensal bacteria in the body such as Escherichia coli and Staphylococcus aureus. This study used a qualitative data collection method with the type of experimental laboratory research to isolate the endophytic bacteria andaliman which had been tested against the pathogenic bacteria Escherichia coli and Staphylococcus aureus. The initial stage were isolation of endophytic bacteria and observation of colony characteristics, after obtaining isolates with different colony characteristics, a Gram stain test and a antagonist test for pathogenic bacteria were carried out. In this study, 252 colonies grew and there were 85 isolates with different colony characteristics. From all the isolates, there were two isolates that could inhibit the growth of Escherichia coli and seventeen isolates that could inhibit the growth of Staphylococcus aureus.